2021
DOI: 10.1038/s41467-021-21485-w
|View full text |Cite
|
Sign up to set email alerts
|

Data linkage to evaluate the long-term risk of HIV infection in individuals seeking post-exposure prophylaxis

Abstract: Evidence on the long-term risk of HIV infection in individuals taking HIV post-exposure prophylaxis remains limited. In this retrospective data linkage study, we evaluate the occurrence of HIV infection in 975 individuals who sought post-exposure prophylaxis in a tertiary hospital between 2007 and 2013. Using privacy preserving probabilistic linkage, we link these 975 records with two observational databases providing data on HIV events (Zurich Primary HIV Infection study and the Swiss HIV Cohort Study). This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Unlike experimental data and observational research studies, program data reflect the realities of day-to-day service delivery, and may often be messy and incomplete [81]. This limitation may inhibit the ability to link programmatic records with unique individuals over time [82,83]. Moreover, aggregate-level data reported through HIV programs may implicate specific interpretations of HIV metrics [41].…”
Section: Using Big Data Science To Focus the Hiv Response Requires Co...mentioning
confidence: 99%
“…Unlike experimental data and observational research studies, program data reflect the realities of day-to-day service delivery, and may often be messy and incomplete [81]. This limitation may inhibit the ability to link programmatic records with unique individuals over time [82,83]. Moreover, aggregate-level data reported through HIV programs may implicate specific interpretations of HIV metrics [41].…”
Section: Using Big Data Science To Focus the Hiv Response Requires Co...mentioning
confidence: 99%
“…Sato et al reported that low C-reactive protein level, immune-related adverse events, high albumin level, high lymphocyte count, and differentiated histological type may affect outcomes (7). In addition, several reports have also reported that CD8 and the tumor mutation burden could be biomarkers for patients with GC using ICIs (8,9). However, biomarker identification from a pathological perspective also has the problem of heterogeneous expression within the tumor (10).…”
mentioning
confidence: 99%